Ensino Médio e Filosofia: contribuições da Filosofia da Libertação para a formação da autonomia dos estudantes, na percepção dos professores - Chacon, Jerry Adriano Villanova (2017)
This dissertation parts from the problem of the recurrent difficulty of autonomy development of students in High School. It brings it as a hypotheses that liberation philosophy can help in the construction of this autonomy. The aim is to research how teachers who are teaching from the liberation philosophy perceive the pedagogical task of developing autonomy with their students, and to what extent and how the practice of these teachers can bring future contributions for the teaching of Philosophy itself. It discusses possible contributions of liberation philosophy to the promotion of autonomy of high school students. In this sense it is justified by the existing relationship between liberation philosophy and the critical theories of curriculum with the freirean project of education as a process of liberation. For the elaboration of this dissertation, the argumentative movement started with the resumption of the historical trajectory of education in Brazil with emphasis on High School, with critical analysis of the tactics that help the understanding of current problems of High School. It was developed in continuity to the analysis of the traces of youth in a dialogue with several areas of knowledge. Analysis were carried out about theories of curriculum and focus was given on the positions brought by Michael Apple. There is in the dissertation a constant dialogue between the perspectives of Dussel and Freire, being listed moments in which Dussel takes Freire as a basis for reflection. Finally, it is given the content analysis of the interviews granted by teachers with experience in philosophy teaching in High School who work based on critical theories in a more specific philosophy of liberation